Aging histological changes in the cartilages of the cricoarytenoid joint - Dedivitis,Rogério Aparecido (2004)
PURPOSE: Analysis of ossification, bone marrow formation, perichondrium thickness, muscle fibers, collagen fibers and elastic fibers quantities of cricoid and arytenoid cartilages. Design: Correlation morphologic study. METHODS: Twenty-four cricoarytenoid joints were obtained from Caucasian male fresh cadavers divided into three groups with eight specimens in each: group I - adolescents, from 15 to 20; group II - adults, from 25 to 35; and group III - elderly, from 60 to 75. The specimens were stained with H-E; trichrome; Picrosirius; and elastic stain. Histometry was performed for quantitative analysis. Bonferroni Test, Fisher Test and the Variance Analysis were used. RESULTS: At the microscopic analysis, the group I specimens presented typical hyaline cartilage, thin perichondrium, bulky muscle fibers and were surrounded by collagen fibers. In group II, there were ossification in small well defined central areas of four specimens, with lamellar bone tissue. In two of these cases there were central bone cavity full of fat tissue. The other parameters were similar to group I. In group III, most part of hyaline cartilage was replaced by typical lamellar bone tissue with poorly outlined haversian systems. Hematopoietic tissue was noted in six cases and fat tissue in the other two. Perichondrium was thicker. Small muscle fibers were smaller and surrounded by collagen in great quantity. Elastic fibers were present in small quantity in the outer portion of perichondrium in all the groups. CONCLUSIONS: In spite of its lack in adolescence, ossification occurs in cricoid and arytenoid cartilages during adulthood and intensifies with age; bone marrow is formed in ossification tissue with hematopoietic tissue in group III; perichondrium becomes thicker in group III; muscle tissue atrophies in group III and is replaced by collagen fibers; these fibers thicken with age; and elastic fibers is always present in the perichondrium in low quantity.